Relações filogenéticas do gênero Apistogramma (Teleostei, Cichlidae) e filogeografia da espécie Apistogramma agassizi - Britzke, Ricardo [UNESP] (2015)
Introduction: Prematurity is the leading cause of neonatal mortality and serious neonatal morbidity worldwide and the risk is inversely proportional to gestational age at birth. Several studies demonstrate the role of innate immune response and Toll-like receptors (TLRs) in normal and complicated pregnancies, however most studies have focused on the tissues of the maternal-fetal interface. Research of the expression of TLRs in gestational tissues is of great importance for understanding the involvement of innate immunity in normal pregnancies and adverse pregnancy outcomes, but the analysis of these tissues allows for results only after the complete resolution of gestation. In this scenario, a potential biological sample of interest for analysis of TLRs in the ongoing gestation are maternal peripheral blood cells, since they play a crucial role in the immune system and express high levels of many of the TLRs. Main: Evaluate the profile of gene expression of TLR-1, -2, -4 and -6 in peripheral blood mononuclear cells (PBMCs) and polymorphonuclear cells (PMNs) and compare these expressions between preterm and term pregnancies. Materials and methods: 119 normal pregnant women were included in the study, subdivided into three groups according to the gestational trimester. In addition, 20 pregnant women in preterm labor and 18 pregnant women at term were evaluated. Gene expression analysis was performed by real-time PCR and protein expression evaluation by flow cytometry. Statistical analyses were performed using the nonparametric Kruskal-Wallis and Mann-Whitney tests by SigmaStat 3.1 software. Results: Regarding PBMCs, there were no significant differences in gene and protein expressions of TLR-1, TLR-2, TLR-4 and TLR-6 among the trimesters. The same was observed when comparing PBMCs of preterm and term pregnancies. In relation to neutrophils, gene and protein expressions of TLR-1, TLR-2, TLR-4 and TLR-6 remained unchanged throughout normal ...